Trajectory and outcomes of speech language therapy in the Prader-Willi syndrome (PWS): case report - Misquiatti, Andréa Regina Nunes [UNESP]; Cristovão, Melina Pavini; Brito, Maria Claudia (Jornal Da Sociedade Brasileira De Fonoaudiologia, 2011)
The aim of this study was to describe the trajectory and the outcomes of speech-language therapy in Prader-Willi syndrome through a longitudinal study of the case of an 8 year-old boy, along four years of speech-language therapy follow-up. The therapy sessions were filmed and documental analysis of information from the child's records regarding anamnesis, evaluation and speech-language therapy reports and multidisciplinary evaluations were carried out. The child presented typical characteristics of Prader-Willi syndrome, such as obesity, hyperfagia, anxiety, behavioral problems and self aggression episodes. Speech-language pathology evaluation showed orofacial hypotony, sialorrhea, hypernasal voice, cognitive deficits, oral comprehension difficulties, communication using gestures and unintelligible isolated words. Initially, speech-language therapy had the aim to promote the language development emphasizing social interaction through recreational activities. With the evolution of the case, the main focus became the development of conversation and narrative abilities. It were observed improvements in attention, symbolic play, social contact and behavior. Moreover, there was an increase in vocabulary, and evolution in oral comprehension and the development of narrative abilities. Hence, speech-language pathology intervention in the case described was effective in different linguistic levels, regarding phonological, syntactic, lexical and pragmatic abilities.